2009 IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2009
DOI: 10.1109/isbi.2009.5193029
|View full text |Cite
|
Sign up to set email alerts
|

A non-parametric approach to automatic change detection in MRI images of the brain

Abstract: We present a novel approach to change detection between two brain MRI scans (reference and target.) The proposed method uses a single modality to find subtle changes; and does not require prior knowledge (learning) of the type of changes to be sought. The method is based on the computation of a local kernel from the reference image, which measures the likeness of a pixel to its surroundings. This kernel is then used as a feature and compared against analogous features from the target image. This comparison is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…The Seo and Milanfar method 4 obtained an average value of 0.879 for SI. As an overall measure of performance, they were able to achieve sensitivity ¼ 0.877, specificity ¼ 0.998, and similarity index ðSIÞ ¼ 0.879.…”
Section: Performance Analysis For Synthetic Imagesmentioning
confidence: 98%
See 2 more Smart Citations
“…The Seo and Milanfar method 4 obtained an average value of 0.879 for SI. As an overall measure of performance, they were able to achieve sensitivity ¼ 0.877, specificity ¼ 0.998, and similarity index ðSIÞ ¼ 0.879.…”
Section: Performance Analysis For Synthetic Imagesmentioning
confidence: 98%
“…4 Rousseau et al 13 evaluated the performance of their methods on simulated lesion images and reported their SI (kapa index) value of around 0.75. Shen et al…”
Section: Performance Analysis For Synthetic Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a recent survey, see [83]. Actually, change detection is of significant interest in an increasing number of applications, such as video-surveillance (e.g., in airports, museums, shops, etc), medical diagnosis [18,81,45,88,90], cell biology imaging [78,19] and remote sensing [23,54]. The challenge lies in distinguishing between meaningful changes related to unusual scene events and changes corresponding to camera motion, camera noise or atmospheric/lighting conditions.…”
Section: Previous Workmentioning
confidence: 99%
“…7.29, our approach produces similar detection masks if the search windows is higher than 5 × 5 pixels. In future work, we plan to compare these results to those obtained by more dedicated methods [88,90] in medical imaging. 8.…”
Section: -Neighborhood System) Asmentioning
confidence: 99%